Determinant Life Style, Financial Literacy, Social Environment Dan Media Sosial Terhadap Consumptive Behavior Generasi Z Di Kabupaten Pasuruan - Mashudi Azrullah Hudi; Khamdan Suriyok; Ninik Churniawati (Institut Teknologi dan Bisnis Yadika, 2026)
The rapid development of digital technology has driven changes in various aspects of life, including consumption activities and the shopping behavior of society. This study aims to analyze the effect of lifestyle, financial literacy, social environment, and social media on the consumptive behavior of Generation Z in Pasuruan Regency. The research employs a quantitative approach using purposive sampling with 65 respondents categorized as Generation Z. Data were collected through Likert-scale questionnaires and analyzed using SPSS, including validity tests, reliability tests, multiple linear regression, as well as t-test and F-test. The results show that lifestyle, financial literacy, social environment, and social media simultaneously have a significant effect on consumptive behavior. Partially, financial literacy, social environment, and social media have a positive and significant effect, while lifestyle has no significant effect. Financial literacy is identified as the most dominant variable influencing consumptive behavior. This study indicates that consumptive behavior is influenced not only by internal factors but also by external factors such as social environment and digital media development.